Pediatric Primary Follicular Mucinosis: Further Evidence of its Relationship with Mycosis Fungoides. Issue 6 (14th March 2013) - Santos‐Briz, Angel; Cañueto, Javier; García‐Dorado, Jesus; Teresa Alonso, M.; Balanzategui, Ana; González‐Díaz, Marcos
Abstract Follicular mucinosis (FM) is an uncommon reaction pattern in which the accumulation of mucin in the follicular epithelium is the main pathologic finding. FM may be idiopathic (primary follicular mucinosis [PFM]), in association with mycosis fungoides or cutaneous T‐cell lymphoma, or in association with other neoplastic and inflammatory conditions. Herein we report a case of PFM with identical T‐cell clone rearrangement at anatomically distinct sites, supporting the idea that some authors have proposed, that FM may represent a low‐grade lymphoproliferative disease related to mycoses fungoides with favorable prognosis.